The Implementation of Team-based Learning IDLE Digital Technology-based Devices in Developing Speaking Skills - Konder Manurung; Aminah Aminah; Wahyudin Wahyudin; Grace Novenasari Manurung (Universitas Cokroaminoto Palopo, 2025)
This study aims to enhance students’ speaking skills in an academic setting by applying the Team-based Learning Model and describe how they perceive the implementation of IDLE digital technology-based devices in the application of the team-based learning model. Mixed Method research is used in this investigation. An experimental method was used to collect quantitative data, applying the Team-based Learning model to teach speaking skills to two student groups, which were selected using a probability sampling technique. Questionnaires and oral tests were used to gather quantitative data, while qualitative data was collected through focus group discussions and interviews. The quantitative data was analyzed using descriptive statistics with SPSS for Windows, and the qualitative data, which focuses on the problems and the objectives of the research, was analyzed using Content Analysis. The results of the data analysis show more students passed the Speaking in Academic Context Course than the students did in the previous academic years. The passing scores are between 71 to 76 and 86 to 100, or grades B (Good) and A (Very Good). According to the findings of data analysis on student perceptions obtained from questionnaires, students used several IDLE digital technology-based devices to complete projects, used the IDLE digital technology-based devices for fairly effective periods, between 30 minutes and over an hour per day, and used them for both receptive and productive activities individually and in group. The findings imply that the effective selection of teaching models and instructional media, especially the application of IDLE digital technology-based devices, is needed to motivate students to learn individually and in groups.